1995
DOI: 10.1897/1552-8618(1995)14[1591:uojtrt]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Use of Joint Toxic Response to Define the Primary Mode of Toxic Action for Diverse Industrial Organic Chemicals

Abstract: An important aspect of understanding how multiple toxicants jointly act involves defining the primary mode of toxic action for the chemicals of interest. We have explored the use of 96-h acute toxicity tests with juvenile fathead minnows and primarily binary chemical mixtures to define the primary acute mode of toxic action for diverse industrial organic chemicals. Our investigation mainly considered the two special cases of noninteractive joint action known as concentration (simple similar) and response (inde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
96
2
1

Year Published

1997
1997
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 61 publications
(102 citation statements)
references
References 11 publications
3
96
2
1
Order By: Relevance
“…Regardless of agreement with detailed biochemical investigations, our results do not agree with many ecotoxicologic studies, which frequently classify chlorophenols as narcotic compounds because of their high lipophilicity [17]. To some extent, this may be true, because a general shift towards narcotic action occurs as hydrophobicity increases [20]. These quantitative structure-activity relationship (QSAR)-based studies have been criticized recently by Russom et al [2], who concluded that many classification schemes and QSARs have been based on chemical classes of compounds, which can be difficult to defend from a toxicologic perspective.…”
Section: Chemical Accumulation and Effects On Organismsmentioning
confidence: 99%
See 4 more Smart Citations
“…Regardless of agreement with detailed biochemical investigations, our results do not agree with many ecotoxicologic studies, which frequently classify chlorophenols as narcotic compounds because of their high lipophilicity [17]. To some extent, this may be true, because a general shift towards narcotic action occurs as hydrophobicity increases [20]. These quantitative structure-activity relationship (QSAR)-based studies have been criticized recently by Russom et al [2], who concluded that many classification schemes and QSARs have been based on chemical classes of compounds, which can be difficult to defend from a toxicologic perspective.…”
Section: Chemical Accumulation and Effects On Organismsmentioning
confidence: 99%
“…Therefore, the compounds selected in this study represent aromatic molecules with different substitution patterns or different amounts of the same substituent. 2,4-Dinitrophenol (2,4-DNP) and pentachlorophenol (PCP) are known uncouplers of oxidative phosphorylation and are commonly used as reference chemicals for this mechanism [9,20]. 1,2,4-Trichlorobenzene (1,2,4-TCB) is widely used as an example of a narcotic chemical [6,8,20].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations